Capital-imperialism and the expansion of the Brazilian insurance sector in the 21st century - Chaves, Rossi Henrique Soares; Ferraz, Deise Luiza da Silva; Ferraz, Janaynna de Moura (Argumentum, 2024)
The article analyses the Brazilian insurance sector in the 21st century, concomitant with the rise of capital-imperialism in Brazil. It explores the concept of capital-imperialism, referring to the recent post-1980 expansion of capitalism. Utilising historical-dialectical materialism, it examines reports on banks and insurance companies to demonstrate the centralisation of the insurance sector and its ties to other financial activities. The study focuses on key segments: a) supplementary health (private health plans); b) personal coverage (private pensions); and c) elementary branches (car insurance). The findings highlight how interconnections between insurance companies, the state, and banks, contribute to the process of the accumulation and centralisation of capital within major global conglomerates operating across the insurance, banking, and financial sectors.